A method for the calculation of the adjoint function in cold neutron sources and its applications. (March 2020) - Márquez, Ariel; Cantargi, Florencia
Highlights: We developed a method for the calculation of the adjoint function in moderators. The method (MC-CHAR) was used for the optimization of a cold neutron source. The results allowed to identify and remove low importance regions of the system. We estimated the intensity change due to geometry modification with a 4% accuracy. Abstract: The optimization process of a cold neutron source (CNS) commonly involves many design variables, such as cold moderator shape and volume, nuclear heating of the moderator and structures, positioning of the device relative to the reactor core, among others. In this research, we develop Monte Carlo techniques to calculate the adjoint neutron function in the cold moderator, when the source of importance is given by neutrons reaching the extraction surface with certain energy and angle requirements. As a relevant application example, the case of a liquid Deuterium CNS was studied, obtaining a detailed transport analysis including adjoint maps that reveal which portions of the moderator are effective to produce required or "important" neutrons. We also show how to make use of this information to modify the geometry of the CNS and to estimate the change in intensity introduced by such modifications.